LINGUODIDACTIC ISSUES OF FOREIGN LANGUAGE TEACHING IN THE SYSTEM OF CONTINUOUS EDUCATION (GENERAL EDUCATION SCHOOLS, ACADEMIC LYCEUMS AND VOCATIONAL SCHOOLS) (Web of Teachers: Inderscience Research, 2026)
This article examines the role of foreign language teaching within the system of continuous education and highlights its strategic importance in the modern globalized world. The study analyzes the theoretical foundations of linguodidactics, including communicative competence, intercultural communication, and learner-centered approaches. Special attention is given to the stages of foreign language education in Uzbekistan, where language proficiency is developed progressively from schools to higher education according to CEFR standards. The article also discusses modern teaching methods such as CLIL and ESP, as well as innovative technologies, digital platforms, and artificial intelligence in language learning. Furthermore, it identifies existing linguodidactic challenges and proposes innovative solutions aimed at improving the quality and effectiveness of foreign language education.